Manajemen Pendidikan Islam: Membangun Generasi Rabbani di Era Digital - Lesnawati, Lesnawati; Khadafie, Muammar (Jurnal Manajemen dan Budaya, 2025)
This research aims to understand and describe the management of Islamic education at SDIT Samawa Qur'ani, focusing on efforts to build a Rabbani generation in the digital era. This research uses a qualitative method with a phenomenological approach. The data collection techniques used were in-depth interviews with teachers, staff, students, and parents, participant observation in class and religious activities, and document studies related to the curriculum, learning programs, and activity reports of SDIT Samawa Qur'ani. The data analysis technique used is thematic analysis. The results show that SDIT Samawa Qur'ani implements comprehensive Islamic education management, with a focus on instilling Islamic values and developing student character. Efforts to build a Rabbani generation in the digital era are carried out through various programs and activities, such as the integration of technology in learning, Islamic value-based character development, and spiritual mentoring of students. This research contributes to understanding and improving the effectiveness of Islamic education management at SDIT Samawa Qur'ani, with a focus on efforts to build a generation of Rabbani in the digital era.